The taxonomy and bioacoustics of the elusive crickets from the genus Pendleburyella Chopard, 1969 (Gryllidae: Pentacentrinae) - Tan, Ming Kai; Muhammad, Amira Aqilah; Wahab, Rodzay Bin Haji Abdul (Zootaxa, 2023)
The taxonomy of poorly known crickets from the genus Pendleburyella Chopard, 1969 (Gryllidae, Pentacentrinae) is reviewed. The type specimens of described species were re-located and re-examined. Based on more recent collections, we describe two new species: Pendleburyella eirmosa sp. nov. and Pendleburyella pimela sp. nov., from Brunei Darussalam and Singapore respectively. The new material also allowed us to examine the male genitalia and describe the male calling song of the genus for the first time.